Pemanfaatan SATAID Untuk Analisa Atmosfer di Wilayah Perairan: Budi Prasetyo dan Nikita Pusparini - Budi Prasetyo Budi Prasetyo; Nikita Pusparini Nikita Pusparini (Jurnal Fisika dan Aplikasinya, 2018)
Marine activity is affected by weather condition and state of sea. Weather analysis satellite is very important for monitoring atmospheric dynamics in global, regional, and local scale because it has a high spatial and temporal resolution. One of application which can be used for analysis satellite imagery is SATAID (Satellite Animation and Interactive Diagnosis). This paper studied about utilization of of SATAID data for analyzing atmosphere condition in case study of KM Sakinah sinking boat on May 16th 2012 at16.00 UTC. We used SATAID, precipitation estimation data from Tropical Rainfall Measuring Mission (TRMM) satelite, weather condition from Belawan Marine Station synoptic observation, wind and wave height data on May 16th 2012. The results showed that SATAID was very useful for analyzing atmosphere condition in waters area. Top cloud temperature around the incident location reached -780 C during incident, so we estimated that Cumulonimbus (Cb) cloud existed. The potential vorticity and showalter stability index showed that atmosphere condition around incident location was labil, so it had more chance to be raining heavily accompanied by thunderstorm (TS) and strong wind. The observed rain cloud had already covered around the incident location since 15.00 UTC and then reached the mature phase at 16.00 UTC. Satellite TRMM data and obsevation data from Belawan Coast showed that weather condition during incident (16.00 UTC) was moderate rain with TS.